Saline solution concentration measurement based on contact angle approach - Klongratog, Bhanupol; Srongprapa, Anupong; Mannaramit, Padet; Leelaphaiboon, Mongkol (My University, 2017)
There are a number of factors that affect the quality control of an osmotic product. One of these is the concentration of the osmotic solution. There are several ways to measure solution concentration, such as optical measurement method, freezing point temperature measurement method, wave principle measurement method, viscosity and specific gravity measurement method. Saline solution concentration of the osmotic solution based on contact angle. The experiments showed whenever the saline solution concentration increased, the contact angle measured on the acrylic substrate increased as well. Their relation is also the linear correlation. Lastly, the developed software evaluated the saline solution concentration based on the contact angle close to the prepared saline solution concentration. The measured concentration was linear correlation with R-squared value of 0.996 that can be accurately applied on concentrations of 5% to 30% with maximum error of 4.72%.
Keywords: Concentration measurement; Contact angle; Saline Solution